Emotional and behavioural difficulties in young Children with and without developmental delay: a bi-national perspective - Einfeld, S; Emerson, Eric (My University, 2010)
Background: Relatively high rates of emotional and behavioural difficulties have been reported among children with intellectual or developmental disabilities. Little is known about nature of the relationship between cognitive development and psychopathology in very young children. Methods: Secondary analysis of data from the first two waves of the UK’s Millennium Cohort Study (n = 11,389) and the first two waves of the Longitudinal Study of Australian Children (n = 4,606). Results: Two- to three-year old children with developmental delay show significantly higher rates of emotional and behavioural difficulties than their peers. These differences appear to reflect a general association between cognitive performance and emotional/behavioural difficulties in the bottom half of the ability spectrum and threshold-based discontinuities within the bottom 3% of the distribution. In the UK, but to a much lesser extent in Australia, higher rates of emotional and behavioural difficulties among children with developmental delay may be partially attributed to greater risk of exposure to adverse socio-economic circumstances. Conclusions: The results highlight the potential value of targeted preventative interventions for young children with developmental delay.
Journal of Child Psychology and Psychiatry
Keywords: Child Development; Child Development -- Behaviour; Childhood and child development; Child Development; Behaviour; Childhood and child development